2016
DOI: 10.7324/japs.2016.60503
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella Spp. in Feed and Their Antibiotic Susceptibility for Alternative Therapy

Abstract: In the study, about 695 samples comprising (fish powder: 320 samples, blood meal: 41 samples, bone meal: 123 samples), finished feed (pellets of pig feed: 213 samples) were collected and detected by polymerase chain reaction (PCR). Isolation prevalence in fish powder, blood meal, bone meal, finished feed was 23(7.19 %), 9 (21.95%), 48 (39.67%), 2 (0.94%) respectively. These Salmonella showed different antibiotic sensitivities to erythromycin, ampicillin, penicillin, ciprofloxacin. However, all these strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The protocol was followed as the previous study. 21 The same strains that showed many serovars with the sulfonamide resistance were used to the detect sul1 and sul2 by PCR to clarify or find out more whether sul1, sul2 or both could affect the resistance as many previous studies concluded before.…”
Section: Salmonella Spp Isolation and Identificationmentioning
confidence: 99%
“…The protocol was followed as the previous study. 21 The same strains that showed many serovars with the sulfonamide resistance were used to the detect sul1 and sul2 by PCR to clarify or find out more whether sul1, sul2 or both could affect the resistance as many previous studies concluded before.…”
Section: Salmonella Spp Isolation and Identificationmentioning
confidence: 99%
“…Salmonella persists in a wide range of feedstuffs for a long period (Abd El-Ghany et al 2015). Therefore, detection and elimination of Salmonella in feed are necessary in the processing chain guarantees (Vu et al 2016). Since all feed ingredients can be potential Salmonella source, decontamination steps are essential to prevent spreading of contaminated feed to production animals (Sauli et al 2005;Hald et al 2012;Vukmirović et al 2017).…”
Section: Introductionmentioning
confidence: 99%